2015
DOI: 10.30649/denta.v9i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Terapi Oksigen Hiperbarik Terhadap Jumlah Sel Osteosit Pada Daerah Tekanan Saat Pergerakan Gigi Ortodonti

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…TOHB is combined with a gel extracted from a Chana Striata, the main component that regulates the connective tissue found inside the Chana Striata. Albumin in Channa Striata can increase angiogenesis, which is a TOHB mechanism in promoting trauma wounds in the area so that a TOHB combination and a stylistic gel of cork significantly increase the effectiveness of treatment [14]. This is due to combined hyperbaric oxygen therapy 2.4 at systemically, and stylistic Channa Striata extract and synergistically increasing fibroblasts' proliferation in the pressure and pull areas.…”
Section: Discussionmentioning
confidence: 99%
“…TOHB is combined with a gel extracted from a Chana Striata, the main component that regulates the connective tissue found inside the Chana Striata. Albumin in Channa Striata can increase angiogenesis, which is a TOHB mechanism in promoting trauma wounds in the area so that a TOHB combination and a stylistic gel of cork significantly increase the effectiveness of treatment [14]. This is due to combined hyperbaric oxygen therapy 2.4 at systemically, and stylistic Channa Striata extract and synergistically increasing fibroblasts' proliferation in the pressure and pull areas.…”
Section: Discussionmentioning
confidence: 99%
“…13 14 15 These biomarkers provide insight into osteogenesis and osteoclast genesis molecular and cellular biology in response to orthodontic mechanical pressures. In addition, parameters or biomarkers used to analyze in the included articles comprised AP), 16 17 collagen synthesis, 16 osteoblast, 18 osteoclast, 17 osteocyte, 19 type I collagen, 20 VEGF, 21 osteocalcin, 21 fibroblast, 18 matrix metalloproteinase-8 (MMP-8), 22 transforming growth factor (TGF)-β, 22 partial pressure of oxygen (pO 2 ), 16 partial pressure of carbon dioxide (pCO 2 ), 16 trabecular bone density, 23 24 teeth mobility, 25 PDL width, 18 number of blood vessels, 18 and TNF receptor associated factor 6 (TRAF-6). 17 From this perspective, it can be concluded that some other biomarkers involved in the orthodontic biological process might be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Salah and Eid used 20 orthodontic patients to evaluate the effect of HBOT on tooth mobility during orthodontic treatment. 25 The other studies used animals (Sprague-Dawley rats, 16 23 dogs, 24 guinea pigs, 18 19 21 42 and Cavia cobaya). 17 20 22 HBOT's effects got more investigated during inactive phase of orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%